Synthesis of graphene/SiO2@polypyrrole nanocomposites and their application for Cr(VI) removal in aqueous solution. (April 2018) - Fang, Wei; Jiang, Xianying; Luo, Hanjin; Geng, Junjie
Abstract: A novel hybrid nanocomposite, polypyrrole nanoparticles (PPy) anchored on the graphene/silica nanosheets with the high specific surface area (polypyrrole-graphene/silica, GS-PPy), was synthesized by a facile in situ polymerization and shows great potential to remove hexavalent chromium [Cr(VI)] in aqueous solutions. Characterizations by XRD, TEM, SEM, BET, FT-IR and XPS, have confirmed that the PPy nanoparticles were well-distributed on the surface of GS nanosheets. The effects of pH, contact time, the concentration of Cr(VI), temperature, coexisting ions and the number of adsorption-desorption cycles were studied. The maximum adsorption capacity of the GS-PPy for Cr(VI) was 429.2 mg g −1 at 298 K at pH 2, which was much higher than PPy nanoparticles and other related materials. The adsorption data fitted to the pseudo-second-order model and Langmuir isotherm model. The removal mechanism involved in electrostatic attraction, ion exchange and reduction process that partial adsorbed Cr(VI) was reduced to Cr(III). And Cr(III) was still retained on the surface of GS-PPy. The GS-PPy nanocomposite will be a potential candidate for the removal of Cr(VI) from the industrial waste water. Graphical abstract: Image Highlights: Polypyrrole decorated graphene-silica composites were synthesized by a facile in situ polymerization. The maximum adsorption capacity of Cr(VI) on GS-PPy was 429.2 mg g −1 . The Cr(VI) was reduced to low-toxicity Cr(III) by the nitrogen species of PPy. The Cr(III) was immobilized on the surface of GS-PPy due to the synergistic effect of GO, SiO2 and PPy.